A real Van Gogh how the art world struggles with truth - Tromp, Henk 1947-; IG Publishing (Amsterdam Amsterdam University Press, 2010)
Vincent van Gogh's paintings and drawings are fabulously expensive. Millions of people admire his work, but are those masterpieces all genuine? To this day, the international art world struggles to separate the real Van Goghs from the fake ones, and the key question addressed in this book is what may happen to art experts when they publicly voice their opinions on a particular Van Gogh (or not). The story starts with art expert J.B. de la Faille who discovered to his own bewilderment that he had included dozens of fake Van Goghs in his 1928 catalogue raisonné. He wanted to set the record straight, but met with strong resistance from art dealers, collectors, critics, politicians and others, marking the beginning of a fierce clash of interests that had seized the art world for many decades of the twentieth century.
An eye for an eye -- True colors -- Hushing up -- For art's sake -- The expert tamed -- Retaliation -- An uneasy legacy -- Between a rock and a hard place -- Among art experts -- The gift -- The unfinished Vincent.
Originally presented as the author's thesis (doctoral--Universiteit Utrecht, 2006) under the title: De strijd om de echte Vincent van Gogh.
Electronic reproduction.
Keywords: Gogh, Vincent van -- 1853-1890 -- Forgeries; Art -- Forgeries; Art -- Expertising; Art -- Economic aspects; Painting -- Forgeries; Electronic books